"When Have You Ever Grasped Light?" The Novelist Sami Berdugo Baptizes the Reader in Black Ink - Livneh, Yoni (MiKAN, 2017)
Critics tend to describe Sami Berdugo as a novelist who is supposedly immune to external influences. Early critics have evaluated his work based on his ability to XIV express an autonomous artistic voice, disconnected from his biographical background. An analysis of his debut short story "Shouk" demonstrates the ambiguous and ironic way in which Berdugo depicts a mother-son relationship as a conflict between an artist and a character of his own creation. Seemingly, the protagonist narrator uses the narrative medium inadvertently, as if he were an unaware raconteur. "Shouk" obliges its reader to discard this path of interpretation based on the narrator' sethnic labelling; to doubt the way he defines his life alongside his mother as an exemplary a esthetical failure. A second reading of the story extracts a new narrative paradigm: an ars poetica on the young Mizrahi artist. The narrator is characterized as his mother's artistic master who breathes life into her character. A further reading of the story and its auto-reflexive narrative provides new meaning to the text's imagery. Sowing threads, the deceased mother's shroud, an appendix bound tohis mother – all later understood as the umbilical cord that allegorizes the artist's struggle to detach himself from his own biography and wipe off the formal signs of identity forced upon him as his mother's son.